2022
DOI: 10.1186/s12877-022-02752-x
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of people with dementia and mental health during COVID-19: findings from a cross-sectional study

Abstract: Background There is sparse evidence on the impact on vulnerable populations of the COVID-19 pandemic. The aim of our study was to explore burden and mental wellbeing (including depressive, anxiety, and stress symptoms) in caregivers of people with dementia during the first wave of the pandemic in Italy and southern Switzerland, two bordering regions severely hit by the COVID-19 pandemic. Methods We conducted an online cross-sectional survey with fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 45 publications
2
21
0
2
Order By: Relevance
“…Despite these limitations, there are strengths. This study mirrors many other studies that demonstrated worldwide increases in caregiver anxiety, care work, financial difficulty, loneliness, and care work [ 23 , 24 , 25 , 26 , 43 , 78 , 81 , 83 , 84 ]. We used regression analysis and validated scales to examine the factors related to anxiety and then used mediation analysis to test hypotheses about the processes by which giving care can cause anxiety.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite these limitations, there are strengths. This study mirrors many other studies that demonstrated worldwide increases in caregiver anxiety, care work, financial difficulty, loneliness, and care work [ 23 , 24 , 25 , 26 , 43 , 78 , 81 , 83 , 84 ]. We used regression analysis and validated scales to examine the factors related to anxiety and then used mediation analysis to test hypotheses about the processes by which giving care can cause anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…Loneliness and social isolation also increased as the result of public health physical and social distancing protocols [ 23 , 24 , 81 ]. Our findings indicate that the association between frailty and loneliness was also moderated by social loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, distribution of paper questionnaire may require obtaining the physical address of each member via some dementia-related organizations, which would challenge the protection of participants’ privacy. Online surveys with family caregivers of persons with dementia have been used previously in Japan [ 18 ] and other countries [ 19 ]. The study protocol was approved by the appropriate ethics review board and was conducted in accordance with the Helsinki Declaration of 1975 (as revised in 2013).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, research-based evidence is needed to inform COVID-19 policies to help mitigate the impact of the pandemic on people with dementia and their family care partners. However, new publications on dementia continue to report findings primarily based on the early stages of the pandemic with little knowledge of the COVID-19 barriers over time [ 5 , 9 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%